Low density lipoprotein receptor-related protein 1 promotes synthetic phenotype of pulmonary artery smooth muscle cells in pulmonary hypertension - Zucker, Marius Michael; Justus Liebig University Giessen (My University, 2021)
Pulmonary hypertension (PH) is characterized by thickening of the distal pulmonary arteries caused by media hypertrophy, intima proliferation and vascular fibrosis. In regard to media hypertrophy, phenotype switching of pulmonary artery smooth muscle cells (PASMC) has been frequently observed. This phenotype switch usually occurs in response to injury associated with dysfunction of endothelial cells and leads to conversion of contractile PASMC to synthetic PASMC. Synthetic PASMC show increased proliferation, migration and expression of extracellular matrix components. Phenotype switching is well described in the context of arteriosclerosis, however, its contribution to the development and progression of PH still remains unexplored. In arteriosclerosis the low density lipoprotein receptor-related protein 1 (LRP1) was described as a scavenger and signaling receptor. By regulating the platelet derived growth factor-BB (PDGF-BB) and the transforming growth factor-β pathways, LRP1 was shown to regulate vascular homeostasis in systemic arteries. Additionally, LRP1 controls recycling and maturation of β1-integrin and thereby influences proliferation and migration of mouse embryonic fibroblasts. This study examines whether LRP1 controls PASMC activities and thus might contribute to vascular remodeling in PH. In this study, LRP1 expression was increased in the lungs of idiopathic pulmonary arterial hypertension (IPAH) patients, hypoxia-exposed mice, and monocrotaline- treated rats. PDGF-BB upregulated LRP1 expression in pulmonary artery smooth muscle cells (PASMC). This effect was reversed by the PDGF-BB neutralizing antibody or the PDGF receptor antagonist. Depletion of LRP1 decreased proliferation of donor and IPAH PASMC in a β1-integrin-dependent manner. Furthermore, LRP1 silencing attenuated the expression of fibronectin and collagen I and increased the levels of α-smooth muscle actin (α-SMA) and myocardin in donor, but not in IPAH, PASMC. In addition, smooth muscle cell-specific LRP1 knockout augmented α-SMA expression in pulmonary vessels and reduced SMC proliferation in 3D ex vivo murine lung tissue cultures. In conclusion, my results indicate that LRP1 promotes dedifferentiation of PASMC and thus contributes to the remodeling of pulmonary vessels in PH. Whether higher LRP1 expression in PASMC from IPAH patients promotes or tries to compensate vascular dysfunction, needs to be answered by future in vivo studies.
Keywords: Pulmonale Hypertonie; ddc:610